METODE ADVOKASI GREEN CAMPUS UNTIRTA - Naniek Afrilla Framanik; Rahmi Winangsih; Rd Nia Kania Kurniawati; Neka Fitriyah; Yoki Yusanto (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2022)
ABSTRACTThe policy regarding Green Campus has been made a foundation regulation by the Rector of Untirta. Furthermore, Planning related to Green Campus has also been made programs. Integrated communication planning is carried out by Untirta in the Green Campus program.This research uses Advocacy Theory, with Post-Positivism Paradigm, Qualitative Approach, Methods: Case Studies, and Data collection techniques carried out by: Observation, Wawancaea, Documentation Studies and Literature Studies. The results of the study, which discusses analysis, are the first step implemented by Untirta to carry out effective advocacy. As is the first step in every action. Advocacy activities designed to have an impact on public policy begin with the availability of accurate information and an in-depth understanding of existing problems, the communities involved, policies and its existence, organizations and pathways that can be accessed to influence influential public figures and decision makers. So far, Untirta is preparing and analyzing. Criteria and indicators used in measuring sustainability programs in the campus environment include: Setting and Infrastructure (SI) (15%), Energy and Climate Change (EC) (21%), Waste (WS) (18%), Water (WR) (10%), Transportation (TR), (6) Education and Research (ED). All planning and activities are listed on the Green Campus Untirta Website The working area of Green Campus Untirta communication planning is published through: Electronic media industry, printing industry, convergent communication (new media), self-image, education, environment, and community awareness.Evaluation is an advocacy effort. So, advocacy efforts must be evaluated as carefully as possible with other campaign activities. Because advocacy activities often produce partial results. The advocacy team needs to regularly and objectively monitor what has been achieved and what remains to be done.The evaluation process can be more important and more difficult than the impact of the evaluation. For evaluation, Untirta has not yet implemented it as a whole, because it is still in the starting level. The final stage in the advocacy model is continuity. Planning for continuity means clarifying long-term goals, maintaining the integrity of coalition functions, and adjusting argumentation data, as changes change. Green Campus Untirta still has a long way to go. Now it has only turned 2 years running and must continue to be improved again, continuously equipped and evaluated periodically.Key Words : Green Campus, Advocation, Evaluation